2011
DOI: 10.1103/physrevlett.107.153902
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory Selection in High Harmonic Generation by Controlling the Phase between Orthogonal Two-Color Fields

Abstract: We demonstrate control of short and long quantum trajectories in high harmonic emission through the use of an orthogonally polarized two color field. By controlling the relative phase φ between the two fields we show via classical and quantum calculations that we can steer the 2-dimensional trajectories to return, or not, to the core and so control the relative strength of the short or long quantum trajectory contribution. In experiments we demonstrate that this leads to robust control over the trajectory cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 18 publications
4
84
0
Order By: Relevance
“…Other applications include the field-free orientation of molecules [16][17][18], the generation of high-harmonic spectra [19][20][21][22] and probing atomic and molecular orbital symmetry [23][24][25].…”
mentioning
confidence: 99%
“…Other applications include the field-free orientation of molecules [16][17][18], the generation of high-harmonic spectra [19][20][21][22] and probing atomic and molecular orbital symmetry [23][24][25].…”
mentioning
confidence: 99%
“…The resulting orthogonally polarized twocolor field was then sent into a 1.5 mm windowless gas cell filled with 10 Torr of argon. By combining 800 and 400 nm for the harmonics generation, odd and even harmonic orders were produced [15][16][17]. The APT was then filtered by using a spatial aperture (2 mm diameter at 0.5 m) and a 200 nm thick Al thin film to remove harmonics below the 11th order.…”
mentioning
confidence: 99%
“…Nevertheless, recent studies on this matter have shown that the "Long"-trajectory harmonics driven by a two-color field can highly benefit the properties of the XUV pulses through the enhancement of the harmonic yield and the control of the spectral phase distribution. The latter can be achieved by changing the relative phase and the intensity ratio between the two colors in the two-color driving field [105,106].…”
Section: Generation Of Asec Pulse Trainsmentioning
confidence: 99%